Diverse responses of belowground internal nitrogen cycling to increasing aridity. (January 2018) - Kou, Dan; Peng, Yunfeng; Wang, Guanqin; Ding, Jinzhi; Chen, Yongliang; Yang, Guibiao; Fang, Kai; Liu, Li; Zhang, Beibei; Müller, Christoph; Zhang, Jinbo; Yang, Yuanhe
Abstract: Belowground microbial nitrogen (N) processes play key roles in regulating terrestrial ecosystem services such as vegetation production, however, our understanding of their responses to climate change remains limited. We determined patterns and controls of five gross N transformation processes along a typical aridity gradient on the Tibetan Plateau. Potential gross N transformation rates responded diversely to the changing aridity. Both mineralization ( M N, average rate: 2.87 mg N kg −1 soil d −1 ) and ammonium immobilization ( I NH4, 3.35 mg N kg −1 soil d −1 ) declined as aridity increased. Autotrophic nitrification ( O NH4, 1.72 mg N kg −1 soil d −1 ) exhibited a bell-shaped pattern along the gradient, with an optimum aridity of 0.53 (1- aridity index (AI)). By contrast, rates of nitrate immobilization ( I NO3, 0.46 mg N kg −1 soil d −1 ) and dissimilatory nitrate reduction to ammonium ( DNRA, 0.10 mg N kg −1 soil d −1 ) did not respond to the changing aridity. These results suggest that predicted increases in aridity will exert different effects on various soil internal N cycling processes, and thus potentially have profound impact on structure and function of dryland ecosystems. Highlights: Belowground microbial nitrogen processes in drylands responded differently to increased aridity. Available substrate exerted a dominant role in regulating mineralization, NH4 + immobilization and nitrification. Nitrate immobilization and dissimilatory nitrate reduction to ammonium did not respond to the changing aridity.